Sistemas de liberação contendo derivado espiro-acridínico: desenvolvimento e avaliação biológica visando a terapia anticancerígena - Melo, Camila de Oliveira (2023)
In recent decades researchers have made significant advances in understanding the pathogenesis, characteristics, and therapies of cancer. Chemotherapy is often the treatment of choice for many types of cancer and for this reason the search for new chemotherapeutic agents is one of the cornerstones in the fight against cancer. Strategies of Medicinal Chemistry associated with other major areas of knowledge, such as biotechnology, facilitate the development of new candidates for drugs or biopharmaceutics. Polymeric nanoparticles have potential for several applications such as diagnosis and drug administration, moreover under adjusted conditions, nanoparticles can accumulate in solid tumours. Inclusion complexes, in addition to improve the apparent solubility of drugs, can decrease toxicity, and protect against premature degradation. This work aims to obtain a nanoparticulate system containing the spiro-acridine derivative (AMTAC-01) and to obtain an inclusion complex to improve the apparent solubility of the derivative. The HPβCD: AMTAC-01 inclusion complex was prepared by the lyophilization method and characterized by the physicochemical techniques of X-ray diffraction (XRD), nuclear magnetic resonance (NMR), scanning electron microscopy (SEM), infrared spectroscopy with Fourier transform (FT-IR), fluorescence spectroscopy, Raman, in addition to phase solubility and molecular docking. The phase solubility showed that as the concentration of cyclodextrins increased the solubility of the drug also increased, suggesting the formation of a complex in the proportion of 1:1 with a stability constant value (ks) of 1145.3 M-1 indicating a good complexation efficiency of AMTAC-01 in cyclodextrins. XRD analysis showed that after complexation AMTAC-01 suffered a decrease in its crystallinity intensity, suggesting a greater dissolution power in biological fluids, this result corroborates the images obtained by the SEM technique that also showed changes in the shape of the crystal after complexation. The other techniques corroborate the confirmation of the inclusion complex formed between HPβCD and AMTAC-01. The nanoparticles were submitted by the method of nanoprecipitation (nanocapsules) and simple emulsion/solvent evaporation (nanospheres) and determined as to their encapsulation efficiency (EE%) and physical-chemical characterization. Cytotoxic activity was performed on human colon cancer cell lines (HCT-116). The results demonstrated that the simple emulsion method was more efficient in trapping the derivative. The techniques used for characterization demonstrated that the presence of the derivative in the nanoparticles decreases its crystallinity, the absence of the endothermic peak of the derivative suggests that there was entrapment of the drug in the polymeric matrix. The cytotoxicity results in HCT-116 cells show that both formulations have cytotoxic activity, with emphasis on the nanospheres. The cell cycle analysis carried out with the imposed nanospheres that the derivative causes interruption of the cell cycle in the Sub G0/G1 phase, being an indication of cell death by apoptosis. The findings found in this work demonstrate the potential activity of the AMTAC-01 derivative in nanoparticles for application in colorectal cancer as its complexation in cyclodextrins. However, further studies are needed to verify its future application as a delivery system for the treatment of cancer.